Faktor – Faktor Yang Berhubungan Dengan Kualitas Tidur Pada Perawat Rawat Inap Rsud Pasar Rebo Tahun 2024 - Ega Ladiesta Pramesti; Ulya Qoulan Karima; Afif Amir Amrullah; Nayla Kamilia Fithri (Health Safety Environment, 2025)
Background: Inpatient nurses in health services have high job demands, changing work patterns, unstable emotions and high workloads can result in poor nurse sleep quality. This study aims to analyze the factors associated with sleep quality in inpatient nurses at Pasar Rebo Hospital. Methods: The research instruments used The Pittsburgh Sleep Quality Index (PSQI) questionnaire, International Physical Activity Questionnaire short-form (IPAQ-sf), Perceived Stress Scale (PSS), physical illness questionnaire, sleep environment, and risky food consumption. The study used chi-square test analysis and multiple logistic regression. Result: The results of multivariate analysis showed that marital status (p-value = 0.000; POR = 52.27), heavy physical activity (p-value = 0.017; POR = 9.476), sleep environment (p-value = 0.012; POR = 4.314), physical illness (p-value = 0.026; POR = 3.529), and gender (p-value = 0.005; POR = 0.184) had an association with sleep quality. Conclusion: In this study, the most related variable was marital status. The hospital can provide rest facilities, educational programmes and activities that are beneficial for nurses so that nurses can improve their sleep quality.  Keywords: Marital status ; Inpatient nurse ; Sleep quality ; Physical activity